2007
DOI: 10.1158/1078-0432.ccr-06-1357
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-18 Fluorodeoxyglucose Positron Emission Tomography Predicts Tumor Differentiation, P-glycoprotein Expression, and Outcome after Resection in Hepatocellular Carcinoma

Abstract: Purpose: To investigate the diagnostic value of fluorine-18 fluorodeoxyglucose positron emission tomography (FDG-PET) for prediction of tumor differentiation, P-glycoprotein (P-gp) expression, and outcome in hepatocellular carcinoma (HCC) patients. Experimental Design: Seventy HCC patients who underwent curative resection were prospectively enrolled in the study. FDG-PET was done 2 weeks preoperatively, and the standardized uptake value (SUV) and the tumor to nontumor SUV ratio (TNR) were calculated from FDG u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
188
2
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 185 publications
(205 citation statements)
references
References 34 publications
11
188
2
4
Order By: Relevance
“…In the Milan or UCSF criteria, size and number of tumors are regarded as representative of the progression and aggressiveness of HCC, with the assumption that more progressive and aggressive HCC is prone to recur by microscopic invasion or seeding. Glucose metabolism as assessed on 18 F-FDG PET is also a factor related to tumor progression or aggressiveness (14)(15)(16)(17)(18). Evident uptake of 18 F-FDG has been observed in poorly differentiated HCC (14)(15)(16)(17), and a correlation between tumor growth rate and 18 F-FDG uptake has also been reported (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Milan or UCSF criteria, size and number of tumors are regarded as representative of the progression and aggressiveness of HCC, with the assumption that more progressive and aggressive HCC is prone to recur by microscopic invasion or seeding. Glucose metabolism as assessed on 18 F-FDG PET is also a factor related to tumor progression or aggressiveness (14)(15)(16)(17)(18). Evident uptake of 18 F-FDG has been observed in poorly differentiated HCC (14)(15)(16)(17), and a correlation between tumor growth rate and 18 F-FDG uptake has also been reported (18).…”
Section: Discussionmentioning
confidence: 99%
“…Because glucose metabolism assessed on 18 F-FDG PET is related to progression or aggressiveness of HCC (14)(15)(16)(17)(18), it is feasible that 18 F-FDG PET uptake, like size and number of tumors, has prognostic value for tumor recurrence in liver transplantation. However, the appropriate application of 18 F-FDG PET or its significance as a prognostic factor has not been investigated in the prediction of tumor recurrence in liver transplantation for HCC.…”
mentioning
confidence: 99%
“…Likewise, in HCC, several investigators have reported that 18 F-FDG uptake evaluated by preoperative PET scan is associated with tumor differentiation as well as recurrences and survival after resection or transplantation. [14][15][16][17] Hence, it is feasible that 18 F-FDG uptake on PET scan, like size and number criterion, might be an important prognostic factor in the establishment of treatment and surveillance plans. However, most studies on HCC and 18 F-FDG-PET have focused primarily on either tumor detection in preoperative settings or prognostic value in patients treated with resection or transplantations.…”
mentioning
confidence: 99%
“…There are few data on the clinical significance of 18 F-FDG-PET in HCC patients who have undergone nonsurgical treatments. 14,15,[17][18][19] Furthermore, to date, there have been no data on the appropriate application of the clinical significance of 18 F-FDG-PET in patients who have undergone localized CCRT followed by repetitive HAIC for locally advanced HCCs.…”
mentioning
confidence: 99%
“…Positron emission tomography imaging could be a good preoperative tool for estimating the post-LT risk of tumor recurrence because histologic grade and vascular invasion cannot be determined preoperatively. 25,26 Lee and associates demonstrated the clinical impact of 18F-FDG PET/CT in 280 patients who underwent living-donor LT at the National Cancer Center. Of 280 patients, 147 (52.5%) had HCC staged beyond the Milan criteria on the basis of pathologic reports.…”
Section: Introductionmentioning
confidence: 99%